Finite Element Analysis of a New Type of Spinal Protection Device for the Prevention and Treatment of Osteoporotic Vertebral Compression Fractures. Issue 3 (11th February 2022) - Che, Mingxue; Wang, Yongjie; Zhao, Yao; Zhang, Shaokun; Yu, Jun; Gong, Weiquan; Zhang, Debao; Liu, Mingxi
Abstract : Objective: To study the effectiveness of a new spinal protection device for preventing and treating osteoporotic vertebral compression fractures (OVCFs) by finite element analysis (FEA). Methods: One healthy volunteer and one patient with 1‐segment lumbar vertebral compression fractures were included in this experimental study. The DICOM files of two different lumbar spiral computed tomography (CT) scans were converted into STL files, and 3D finite element models of the lumbar spine were generated for normal and L1 vertebral fracture spines. A new type of spinal protection device was applied to reduce the stress on the anterior vertebral edge and direct the center of gravity posteriorly. The stress distribution characteristics of different finite element models of the lumbar spine were analyzed, revealing the characteristics of the stress distributed along the spine under the action of the new spinal protection device. Results: Under normal conditions, the stress was mainly distributed in the middle and posterior columns of the spine. When the anterior border of the L1 vertebral body was fractured and collapsed, the stress distribution shifted toward the anterior column due to the center of gravity being directed forward. According to finite element analysis of the spine with the new protection device, the stress in the middle and posterior columns tended to increase, and that in the anterior column decreased. After the new type of spinal fixation device was applied, the stress at the L1 and L2 vertebral endplates decreased to a certain extent, especially that at the L1 vertebral body. The maximum stress on the L1 vertebral body decreased by 20% after the auxiliary device was applied. Conclusions: According to the FEA results, the new spinal protection device can effectively prevent and treat osteoporotic vertebral compression fractures (OVCFs), and can alter the stress distribution in the spine and reduce the stress in the anterior column of the vertebral body, especially in vertebral compression fractures. Abstract : We found that when the anterior border of the L1 vertebral body was fractured and collapsed, the stress distribution shifted toward the anterior column due to the change of the center of gravity. According to finite element analysis of the spine with the new protection device, the stress in the middle and posterior columns tended to increase, and that in the anterior column decreased, indicating that this device can effectively alter the stress distribution in the spine and treat OVCFs.